Analysis of Student Perceptions About Cryptocurrency Assets Viewed from Perceived Costs, Benefits and Risks - Nurmawan, Ahmat; Putri, Rahmah Dianti; Rupaidah, Erlina (FKIP Universitas Lampung, 2023)
This study aims to determine how students' perceptions of cryptocurrency investment assets are viewed from cost perception, benefit perception, and risk perception. This study used quantitative descriptive research method with survey approach. The population in this study is students of the Economic Education Study Program FKIP University of Lampung with a total of 230 students. The sampling technique in this study was Probability Sampling using the Simple Random Sampling technique and a sample of 146 students was obtained. The results stated that students of the Economic Education Study Program FKIP University of Lampung have a good perception of cryptocurrency investment assets in terms of aspects of cost perception and benefit perception. Meanwhile, in terms of risk perception, students of the Economic Education Study Program FKIP University of Lampung have a bad perception of cryptocurrency assets. Seeing the potential and development of financial instruments, students should begin to be sensitive and begin to understand all aspects in it before investing to avoid various kinds of existing risks.Keywords: Benefits, Cryptocurrency Assets. Perception of Costs, RisksDOI: http://dx.doi.org/10.23960/E3J/v6i1.110-117